Investigação da ação bactericida de produtos naturais sobre a bactéria Xylella fastidiosa - Silva, Danielle Fernandes da (2013)
This work describes the study of natural compounds as potential bactericides for control of Xylella fastidiosa which causes the Citrus Variegated Chlorosis (CVC), a disease that causes large losses in brazilian citrus and still does not have a bactericidal specific in the market to combat it. The project was deveped in two stages. The first part of the work was done in vitro, where the compounds naringenina complexed with rutênio and magnésio, separately, hesperidina complexed with magnésio, azadirachtina, hesperidina and naringenina were tested as inhibitors of Xylella fastidiosa growth using the system of microdilution in culture media to detect the minimal inhibitory concetration of these compounds against the bacterium Xylella fastidiosa. These compounds showed, respectively, minimum inhibitory concentrations of 0,19 µM, 0,34 µM, 1,01 µM, 2,1 µM, 3,27 µM e 7,3 µM. In a second phase, the best results obtained in vitro were validated in Vivo experiments, where the bacterium was inoculated into healthy citros plants. After a period of manifestation of disease in plants, these were diagnosed by PCR analysis to identify which plants had been contaminated by the bacterial. After detecting diseased plants through the presence of Xylella fastidiosa s DNA, they were treated with those natural componds and their derivatives that have been tested in vitro. After a period of treatement, the plants to obsorb the metabolites and acted upon these bacteria, a analysis was perfomed by quantitative PCR (qPCR) comparing the amount of bacteria in plants before and after treatment with the bactericide, evaluating the occurrence or not, of the bacterium inibition. The following results were obtained: for naringenina complexed with Mg, 0,8 µM; naringenina complexed with Ru, 1,2 µM; azadirachtina, 1,4 µM; hesperidina, 1,8 µM; naringenina 3,9 µM and cuprum (positive control), 6,3 µM, this for 0,1% of life bacteria. The in vitro results consistent with the results in vivo.